Two Prominent Technology Innovations in the Human Resource Management Improvement: e-HRM and AI-HRM - Winarno, Budi (International Conference On Economics Business Management And Accounting (ICOEMA), 2023)
Technological innovation is increasingly playing an important role for companies to increase their competitive advantage in the digitalization era. One of the areas targeted for company innovation is human resource management (HRM) with to improve employee performance, effectiveness, and productivity. This study then explains the two most prominent forms of technological innovation that can be implemented by companies, namely electronic human resource management (e-HRM) and artificial intelligence human resource management (AI-HRM). The method used by the authors is a qualitative method with a focus on literature review, so we are more focused on the use of secondary data, mainly the international reputable journals. This study shows the results that the utilization of e-HRM and AI-HRM have a significant role in improving the quality of the company’s HR. Instead of replacing the role of employees, these two innovations actually play a role in facilitating and completing their tasks/work. This phenomenon leads to collaboration between technological machines and humans in companies.